Innovative Quranic Teaching Methods Shape Moral Character in Students - Setiawan, Eriko Viksiano; Eni Fariyatul Fahyuni (Indonesian Journal of Islamic Studies, 2024)
General Background: Quranic education plays a crucial role in shaping the religious character of students in Islamic educational institutions. Specific Background: However, the effectiveness of various teaching methods in facilitating student understanding and application of Quranic content remains underexplored. Knowledge Gap: Limited research has been conducted on the specific methodologies employed in Quranic teaching and their impact on character development within Islamic boarding schools. Aims: This study aims to analyze the Quranic education practices at Pondok Wali Barokah and their role in cultivating the religious character of students through effective teaching methods. Results: Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that the teaching methods, particularly Manqul and As-Sama’, significantly enhance students’ comprehension of the Quran and Hadith while fostering attitudes aligned with Islamic teachings. Novelty: This research contributes to the literature by highlighting the practical implications of specific Quranic teaching methodologies on character formation, demonstrating their efficacy in instilling discipline, respect, and moral values in students. Implications: The results suggest that the successful implementation of these methods can serve as a model for Islamic educational institutions seeking to improve character education and cultivate a generation of knowledgeable and morally upright individuals prepared to positively contribute to society. Highlights: Manqul and As-Sama’ enhance Quranic understanding and application. Quranic education fosters respect, discipline, and moral values. Qualitative research reveals significant impacts on students' character development. Keywords: Quranic education, character development, teaching methods, Islamic boarding schools, qualitative research